Symbolic Structure and Personal Myth: Reading a Fernando Opere’s Memorial del olvido (Castilla. Estudios de Literatura, 2012)
When a poet’s creative trajectory is condensed into a single volume critics tend to search for indicators of continuity or breaks within that trajectory. The present article attempts to shed light on some of the thematic foundations that have defined the unique work of the poet Fernando Operé, focusing most importantly on the lyrical protagonist and the mythic-symbolic structure that form the backbone of his work Memorial del Olvido. To this end, we shall take as reference the signposts, direct or indirect, elaborated in mythico-critical studies such as Gilbert Durand’s (1986 and 1993), Campbell’s (1999) model of monomyth, and the ritual-symbolic structures studied principally by Eliade (1999 and 2002) and Bachelard (2000). Following such a procedure, we will be able to prove that the same exegetic models are perfectly valid and applicable to the analysis of a poet’s entire oeuvre, as Charles Mauron has already suggested in his discussion of the concept of personal myth in human creativity at large.